(untitled) (Asian Business Research, 2022)
Since the beginning of the 21st century, developing a low-carbon economy and reducing greenhouse gas emissions have become the consensus of the international community. The modern tax system is a green tax system. In theory, levying a carbon tax has the intrinsic value of internalizing the external cost of carbon emissions, releasing the double dividend of environmental taxation, and supplying internal value of global public goods for addressing climate change. It is of strategic significance to achieve peak carbon dioxide emissions and carbon neutrality, promote high-quality development, build an ecological civilization, ensure the sustainable development of the Chinese nation, and build a community with a shared future for mankind. Some western developed countries have established relatively complete carbon tax systems and accumulated many useful experiences in this regard. Based on the various practices of carbon tax collection in foreign countries, this paper proposes system design suggestions for the introduction of carbon tax in our country from four aspects: tax model, tax scope, tax rate and tax preference, and revenue-neutral recycling.